Current Status and Prospect of Membrane-Based Offshore Floating Photovoltaic Technology - Jiping CHEN; Gang LI; Bo LIU; Hong QIAO (南方能源建设, 2023)
[Introduction] The research and development of offshore floating photovoltaic complies with the needs of national energy strategic development, caters to the background of industry development led by science and technology, and helps the development of emerging economic industrial chain. This paper aims to deeply explore the main components and core technologies of offshore floating photovoltaic system, and provide a theoretical basis for the development of offshore floating photovoltaic in China. [Method] Based on the existing research on offshore floating photovoltaic at home and abroad, this paper refined the relevant construction technology of flexible photovoltaic, verified the commercial feasibility of offshore floating photovoltaic development, introduced the configuration and composition of large-scale offshore floating photovoltaic (LOFPV) system, expounded the hydrodynamic design theory and method basis of flexible membrane structure and mooring system, and showed the typical engineering practice of offshore floating photovoltaic. [Result] Offshore flexible membrane-based floating photovoltaic has many advantages, such as lightweight, miniaturization, high power exchange efficiency and flexible configuration. In addition, the membrane structure is foldable, convenient for transportation, and convenient for installation, and the overall structure has no complex connector, so the system has high reliability and is convenient for operation and maintenance. Relevant achievements of this paper will provide great reference value for the development of China's offshore floating photovoltaic technology. [Conclusion] The functionality and reliability of flexible membrane-based floating photovoltaic construction technology are explained, and this flexible membrane structure will definitely be an important application type of offshore floating photovoltaic in the future.